Cyanobacteria modulated changes and its impact on bioremediation of saline-alkaline soils - Singh, Venus; Singh, DV (Bangladesh Journal of Botany, 2018)
Saline-alkaline (Usar) soils have high pH and undesirable salts on their surface. A halotolerant, heterocystous and nitrogen fixing cyanobacterium Nostoc calcicola Breb. BREB grow successfully on salinealkaline soils of Eastern Uttar Pradesh. Soil pot experimentation has been conducted in laboratory condition to study the reclamation of saline-alkaline soils collected from investigated site. Both sterilized and natural soils were taken in earthen pots to observe the changes in soil properties inoculated with cyanobacteria and gypsum. In such treated soils significant decrease in pH, ECe and Na+ have been observed with cyanobacterial application. There also occurs a significant increase in organic carbon. Experimental reclamation of such soils has been found with cyanobacteria with or without gypsum. N. calcicola + gypsum seem to be a suitable combination for reclamation of saline-alkaline soils. This study highlights that a biological amendment with halotolerant cyanobacteria and gypsum in combination shows better option for bioremediation of saline-alkaline (Usar soils).